How do parents evaluate the quality of education? (Journal of Parents and Teachers, 2025)
The article states that parents can be divided into two groups. On one hand, there are those who focus solely on academics and immediate results, while on the other hand, there are parents who believe that a good grade on the entrance exam does not guarantee success. Many parents would like to forgo certain knowledge for their children in exchange for teaching them the importance of reading, solidarity, and more. Additionally, all of this is compounded by the failures that can be experienced in various situations.
Keywords: parents; academic; failure; knowledge